Skepticism, Mental Disorder and Rationality - Kyriacou, Christos (International journal for the study of skepticism, 2023)
I stipulate and motivate the overlooked problem of demarcating radical skeptics (perceptual and moral) from mentally disordered persons, given that both deny that they know ordinary Moorean propositions (e.g., that they have hands or that killing for fun is morally wrong). Call this ‘the demarcation problem’. In response to the demarcation problem, I develop a novel way to demarcate between mentally disordered persons and radical skeptics in an extensionally adequate way that saves the appearance that radical skeptics are not mentally disordered persons (at least not typically). Finally, I examine how a Moorean, non-skeptical epistemologist would compare radical skeptics with the mentally disordered in terms of what Plantinga calls internal and external rationality. Perhaps surprisingly, by Moorean lights, the mentally disordered fare better than the radical skeptic in terms of (internal) rationality. The upshot is that for Mooreans skeptical philosophy is more of an epistemic evil than mental disorder.